Use of strontium for bovine oocyte activation - Méo, Simone Cristina [UNESP]; Yamazaki, Walt [UNESP]; Leal, Cláudia Lima Verde; Oliveira, João Ademir de [UNESP]; Garcia, Joaquim Mansano [UNESP] (Elsevier B.V., 2005)
Strontium efficiently activates mouse oocytes, however, there is limited information on its use in cattle. Thus, the objective of this study was to establish a suitable protocol for activating bovine oocyte with strontium. For pronuclear development, the absence of calcium and magnesium in the activation medium (TALP) with 10 and 50mM strontium (34.4 and 53.1%, respectively) was superior to the complete TALP (6.5 and 19.4%, respectively). In all activation media, better results were observed with 25 and 50 mM strontium (21.9-53.1 and 19.4-53.1%, respectively). Incubation for 4 h promoted similar results in all strontium concentrations. However, strontium at 15, 20, and 25 mM for 6 and 8 h (40.7, 46.7, and 48.3%, and 29.3, 48.3, and 40.7%, respectively) were superior to control (15.5 and 10%, respectively). After in vitro maturation for 26 h, strontium (S; 20 mM in Ca2+ and Mg2+-free TALP for 6 h), ionomycin + strontium (IS), and strontium + ionomycin (SI) (60, 63.3, and 65%, respectively) were similar in pronuclear development and superior to ionomycin (I; 5 mu M for 5 min; 36.7%). In treatments S and I, only 1 PN zygotes were observed. In treatment S, most of them had 1 and 2 PB (35.7 and 60.7%, respectively), and in treatment I, 0, 1, and 2 PB (14.3, 57.1, and 28.6%, respectively). Most of the zygotes in treatment IS and SI were 1 PN 2 PB (77.4 and 61.6%, respectively). The number of oocytes with clusters of cortical granules was similar in all treated groups (11-29%). Cortical granule exocytosis in treatment IS (68%) was similar to S (54%) and superior to 1, SI, and control (27, 45, and 5.0%, respectively). Cleavage and blastocyst rates were similar for S, I, IS, and SI treatments (61.7-76.7, and 8.3-13.3%, respectively) and the same was observed for ICM, TE, and total cell number, and ICM/total cell ratio (22-25, 64-69, and 86-95, and 0.26-0.27). In conclusion, strontium may be efficiently applied for bovine oocyte activation at 20 mM in Ca2+-and Mg2+-free TALP medium for 6 h.
Keywords: artificial activation; cortical granules; divalent cations; ionomycin; parthenogenetic development